Improving Soil Properties and Yield of Corn (Zea Mays L.) by Application of Organic Amendment on Abandoned Tin-Mining Land in Bangka Island - Asmarhansyah, . (JOURNAL OF TROPICAL SOILS, 2016)
An abandoned land after tin-mining activities are degraded lands with undulating and destructed land scape and low soil fertility status. The objective of this study was to determine the effects of organic amendments on the soil properties, growth, and grain yield of corn (Zea mays L.) on abandoned tin-mining areas in Bangka Island, Bangka Belitung Archipelago. The field experiment was conducted at the abandoned tin-mining areas in Cambai Village, Bangka Belitung Archipelago. Five treatments of organic amendments were applied and replicated three times and laid out in a Randomized Completely Block Design. All treatments were applied with the recommended rate fertilizer of 135 kg N ha-1, 72 kg P2O5 ha-1, and 120 kg K2O ha-1. The treatments were T1= 20 Mg chicken manure ha-1;T2= 20 Mg cattle manure ha-1; T3= 20 Mg rice straw compost ha-1; T4 : 10 Mg of chicken manure ha-1 + 10 Mg rice straw compost ha-1; and T5= 10 Mg cattlemanure ha-1 + 10 Mg rice straw compost ha-1. Application of organic amendments (chicken manure, cattle manure, and rice straw compost) on abandoned tin-mining land improved soil fertility due to the increasing of soil pH and nutrient availability, especially available-P and -K, and exchangeable bases. Application of chicken manure and cattle manure were significantly better than rice straw compost to improving soil fertility, nutrient uptake, growth and yield of maize. Application of cattle manure gave the highest yield of maize, namely 6.24 Mg ha-1.